Accent and Linguistic Prejudice within British Teacher Training. Issue 6 (2nd November 2017) - Baratta, Alex
ABSTRACT: Based on the responses of 32 British teachers, I report on a sample of three teachers who were told to modify their accents to varieties deemed more "professional." The teachers perceive such directives to stem from linguistic prejudice and not merely a need to be understood, and such directives are based on someone else's standards for "linguistic professionalism." Ultimately, I wish to engage with policymakers in order to establish what the linguistic reality is for British teachers in terms of accent, and their linguistic rights in the process. This is an issue that goes beyond the British context and can apply to both L1 and L2 teachers, whenever and wherever they are led to believe that their accent, though they are otherwise fully qualified to teach, is a hindrance. Thus, I report on the British context to address what is potentially a much more widespread issue.